2021
DOI: 10.1021/acsapm.0c01422
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Membrane of CuS/Polyacrylamide–Carboxymethyl Cellulose for Solar Evaporation

Abstract: Solar water evaporation is an environment-friendly and clean way of wastewater treatment and seawater desalination. However, a solar evaporator based on a hydrogel substrate still needs excellent toughness to ensure continuous and stable utilization while achieving a fast evaporation rate. In this research, a solar evaporator based on a dual network hydrogel was fabricated by double chemical cross-linking, consisting of polyacrylamide (PAAm), carboxymethyl cellulose (CMC), and CuS. By utilizing N,N′methylenebi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…33 Commonly, LSPR spectral band can be expanded by hollow structure, asymmetrical design, particlesize shifts, and dielectric surroundings 72 to compensate for the inherent shortcoming of the narrow absorption spectra of plasmonic nanoparticles caused by their specific geometrics. 39 Common plasmonic nanoparticles used as solar absorbers include Ag, [73][74][75][76] Au, 77 CuS, [78][79][80][81] Cu, 44,82 and so on. Recently, Wang et al 26 reported a novel plasmonic Cu7S4-MoS2-Au composite nanoparticle (CMA NP) with broad absorption and high photothermal conversion efficiency, which arises from the coupling effect among Cu7S4, MoS2 and Au, as well as the comprehensive utilization of their advantages(Figures 3a and 3b).…”
Section: Plasmonic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Commonly, LSPR spectral band can be expanded by hollow structure, asymmetrical design, particlesize shifts, and dielectric surroundings 72 to compensate for the inherent shortcoming of the narrow absorption spectra of plasmonic nanoparticles caused by their specific geometrics. 39 Common plasmonic nanoparticles used as solar absorbers include Ag, [73][74][75][76] Au, 77 CuS, [78][79][80][81] Cu, 44,82 and so on. Recently, Wang et al 26 reported a novel plasmonic Cu7S4-MoS2-Au composite nanoparticle (CMA NP) with broad absorption and high photothermal conversion efficiency, which arises from the coupling effect among Cu7S4, MoS2 and Au, as well as the comprehensive utilization of their advantages(Figures 3a and 3b).…”
Section: Plasmonic Nanoparticlesmentioning
confidence: 99%
“…Common plasmonic nanoparticles used as solar absorbers include Ag, 73–76 Au, 77 CuS, 78–81 Cu, 44,82 and so on. Recently, Wang et al 26 reported novel plasmonic Cu 7 S 4 –MoS 2 –Au composite nanoparticles (CMA NPs) with broad absorption and high photothermal conversion efficiency, which arises from the coupling effect among Cu 7 S 4 , MoS 2 and Au, as well as the comprehensive utilization of their advantages (Fig.…”
Section: Solar–thermal Conversion Enhancementmentioning
confidence: 99%
“…Herein, a 3D opened hollow cylinder-like solar evaporator (OHCE) was constructed using hierarchically porous CuS-cellulose composite (CSC) as light absorber. Although various CuS nanostructures have been prepared and utilized as photothermal materials for solar evaporation, [44][45][46][47][48] porous structured CuS has not been explored for fabricating 3D photothermal evaporators. The CSC-coated sheet (Figure S1, Supporting Information) was tailored and wrapped on a steel frame to fabricate an OHCE with four slots on its side evaporation surfaces (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Solar vapor generation (SVG) is one of the most important ways to utilize solar energy [ 1 , 2 , 3 , 4 , 5 ]. In recent years, SVG has attracted much attention due to the increasing demand of fresh water [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The introduction of interface SVG, which is a self-floating solar absorber to float at the water–air interface, further improves the photothermal conversion efficiency of solar energy [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%